2012
DOI: 10.1038/ng.1084
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in CTC1, encoding conserved telomere maintenance component 1, cause Coats plus

Abstract: Coats plus is a highly pleiotropic disorder particularly affecting the eye, brain, bone and gastrointestinal tract. Here, we show that Coats plus results from mutations in CTC1, encoding conserved telomere maintenance component 1, a member of the mammalian homolog of the yeast heterotrimeric CST telomeric capping complex. Consistent with the observation of shortened telomeres in an Arabidopsis CTC1 mutant and the phenotypic overlap of Coats plus with the telomeric maintenance disorders comprising dyskeratosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
237
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 242 publications
(255 citation statements)
references
References 18 publications
1
237
0
6
Order By: Relevance
“…Genetic variants of Stn1 are associated with increased telomere length in leukocytes [7] and expressing a deletion mutant of Stn1 in cancer cells causes telomere lengthening [5], suggesting that Stn1 may be involved in telomere length regulation. Recently, mutations in Ctc1 have been isolated from patients with telomere disorder dyskeratosis congenita (DC) and patients with Coats Plus (CP) syndrome, a complex genetic disease clinically related to DC [8][9][10]. Shortened telomeres were observed in both CP and DC patients carrying Ctc1 mutations [8,10], suggesting that the underlying cause for CP may be related to defective telomere maintenance induced by Ctc1 mutations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic variants of Stn1 are associated with increased telomere length in leukocytes [7] and expressing a deletion mutant of Stn1 in cancer cells causes telomere lengthening [5], suggesting that Stn1 may be involved in telomere length regulation. Recently, mutations in Ctc1 have been isolated from patients with telomere disorder dyskeratosis congenita (DC) and patients with Coats Plus (CP) syndrome, a complex genetic disease clinically related to DC [8][9][10]. Shortened telomeres were observed in both CP and DC patients carrying Ctc1 mutations [8,10], suggesting that the underlying cause for CP may be related to defective telomere maintenance induced by Ctc1 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, mutations in Ctc1 have been isolated from patients with telomere disorder dyskeratosis congenita (DC) and patients with Coats Plus (CP) syndrome, a complex genetic disease clinically related to DC [8][9][10]. Shortened telomeres were observed in both CP and DC patients carrying Ctc1 mutations [8,10], suggesting that the underlying cause for CP may be related to defective telomere maintenance induced by Ctc1 mutations. Though it has been shown that transient depletion of Ctc1 or Stn1 in HeLa leads to telomere instability [3,4], the precise role of human CST complex is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This rare multisystem disorder is thought to encompass both Coats plus and leukoencephalopathy with calcifications and cysts (LCC). 9,10 The key characteristics of this disorder include intracranial calcifications and leukoencephalopathy, retinal vasculature abnormalities, skeletal abnormalities and recurrent gastrointestinal hemorrhage. Dystrophic nails, sparse hair and abnormal skin pigmentation have occasionally been observed in such patients.…”
Section: Introductionmentioning
confidence: 99%
“…Coats plus patients are compound heterozygous for two different CTC1 mutations, with one allele harboring a frameshift mutation and the other a missense variant (Anderson et al., 2012; Keller et al., 2012; Polvi et al., 2012; Walne et al., 2013). Previous analysis of the human CTC1 L1142H mutation relied on transient expression of the mutant in HT1080 cells bearing wild‐type (WT) CTC1 alleles, making it difficult to understand the in vivo effects of this mutation (Chen et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Missense mutations in the human CTC1 gene cause Coats plus (CP), a rare autosomal recessive disorder characterized by retinal telangiectasia, intracranial calcifications, osteopenia, and gastrointestinal bleeding (Anderson et al., 2012; Polvi et al., 2012; Walne et al., 2013). While some CP patients possess very short telomeres and have phenotypes resembling those patients with Dyskeratosis congenita (DC), suggesting that telomere maintenance is also functionally impaired in these patients, telomere lengths in other CP patients are not markedly reduced (Polvi et al., 2012).…”
Section: Introductionmentioning
confidence: 99%